Old English and the lexicography of Old High German - Bulitta, B (2010)
No one who deals with the earliest written records of German would be surprised to encounter Old English words. They are the linguistic remains of the Anglo-Saxon scholars, who came as missionaries and educators to the German speaking Frankish Empire. These scholars mediated the knowledge of religious and scientific Latin texts on the continent and in doing so introduced the practice of adding glosses to these texts in their own language. Colloquial glosses, i.e. (German) translations added to the Latin words, form a substantial part of the earliest preserved vocabulary and are therefore extremely important for the historical lexicology of the German language. Two thirds of all known lenmata of Old High German come from glosses, only one third comes from texts written in German. The lexicographical interpretation of those glosses that are related to the Anglo-Saxon transmission of knowledge faces serious difficulties: Old English and Old High German glosses may occur side by side in the same manuscript. However it is often difficult to decide to which language they actually belong (cfr. for instance the scratched glosses in the Maihinger Book of Gospels from Echternach from the 8th century AD). In the course of the transmission of knowledge, copies of Old English Manuscripts were made by German speaking scribes, but because of difficulties in reading the insular script and because of lack of knowledge of the English language, numerous errors were introduced into the copies (see e.g. the Old English Erfurt Glossary from the 9th century). Graphical and morphological disfigurements and reinterpretations render both the attribution of the actual word forms to a given lemma as well as the interpretatin of morphology and meaning hazardous. As the actual word form may give evidence for the linguistic origin of the copyist, a correct interpretation is quite relevant for the study of early German. How do the dictionaries of Old High German deal with this transitional material? Which of them take it into consideration and how do they present it for their specific purpose? In answering these questions we will focus on the Old High German Dictionary Project of the Saxon Academy of Sciences in Leipzig, which so far published five volumes since 1952, finishing the letter "L".